2006
DOI: 10.1111/j.1540-8175.2006.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Clinical Impact of Live Three‐Dimensional Echocardiography in the Management of Congenital Heart Disease

Abstract: Our study demonstrates that live 3DE, easily performed at the bedside, provides incremental information on patients with a variety of congenital heart lesions. In the clinical scenario, it clarifies the pathology in all its dimensions, particularly in complex lesions with the incremental information having impact on therapeutic decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Three-dimensional echocardiography would appear to be superior to 2-dimensional echocardiography in the measurement of atrial septal defects. 41 cTCD could provide significant information in those situations where a semiquantification of RLS at rest is required. Apart from patients with stroke where RLS during normal breathing could enhance the clinical relevance of PFO, thus explaining the possible occurrence of paradoxical embolism during normal daily activities, discovering a shunt at rest may be important even in other conditions in which paradoxical embolization may play a role, such as during neurosurgical procedures in sitting position, scuba diving, or in ''economy-class'' 42 or platypnea-orthodeoxya syndromes.…”
Section: Discussionmentioning
confidence: 98%
“…Three-dimensional echocardiography would appear to be superior to 2-dimensional echocardiography in the measurement of atrial septal defects. 41 cTCD could provide significant information in those situations where a semiquantification of RLS at rest is required. Apart from patients with stroke where RLS during normal breathing could enhance the clinical relevance of PFO, thus explaining the possible occurrence of paradoxical embolism during normal daily activities, discovering a shunt at rest may be important even in other conditions in which paradoxical embolization may play a role, such as during neurosurgical procedures in sitting position, scuba diving, or in ''economy-class'' 42 or platypnea-orthodeoxya syndromes.…”
Section: Discussionmentioning
confidence: 98%
“…RT-3D TTE and TEE are currently available for visualization of abnormal morphology, assessment of chamber size and ventricular function, and image-guided interventions in the congenital heart disease population [51,[64][65][66][67]. RT-3D TTE provided superior detail of the mural leaflet and anterior commissural abnormalities for the left atrioventricular valve compared with 2D echocardiography.…”
Section: Assessment Of the Ascending Aortamentioning
confidence: 99%
“…Similarly, Cheng et al 47 and Mehmood et al 48 in 38 patients and 10 patients, respectively, demonstrated that sizing of VSDs using 3DE was more highly correlated with surgical findings than the diameter measured by 2DE and accurately defined VSD location, size, and surrounding anatomy in all patients. In complex lesions, De Castro et al 49 reported that the use of real-time 3DE provided incremental information to 2DE in a variety of complex congenital heart lesions which affected therapeutic decision making in 82 patients.…”
Section: Challenges Of 3de Relevant To Vsd Closurementioning
confidence: 99%